Stock Market Liquidity Commonality and its Determinants / Mohammed H M Abuzaid - Abuzaid, Mohammed H.M. (2013)
This study investigates the existence of commonality in the liquidity of an emerging stock market that applies an order-driven trading system. Moreover, this study explores the dynamic relationship between macroeconomic variables and stock market liquidity. In addition, it examines the relation between stock liquidity and expected return. This study examines the market-wide co-movements in liquidity within the Malaysian stock exchange using a broad sample of 125 stocks covering a period of more than 16 years, which is also used in analysing the relation between macroeconomic variables and stock market liquidity. Value-weighted market liquidity variables are used in our estimation. The results show that commonality in liquidity does exist in the Malaysian stock market. To further detect existence of commonality in the Malaysian stock market, the sample is classified into three categories: large, medium, and small companies. Commonality was present within the findings of all three categories. The commonality analysed within the cross-lists, and within the market as a whole, classifies the samples under two categories, one being the crosslisted companies in both Malaysian and foreign markets, and the other identified as companies that are exclusively listed on the Malaysian stock market. To the best of our knowledge, this is the first analysis of the association between market liquidity and market variables (return, trading activity, and volatility), and macroeconomic variables (industrial production, real effective exchange rate, investment portfolio, and interest rate), in an emerging market, conducted through the VAR model. The vector autoregression analysis was first conducted between the market liquidity and market variables; and again it was conducted in one vector consisting of market liquidity and macroeconomic variables. The sub-samples analysis have shown that the dynamic relation linking both market and macroeconomic variables to market liquidity vary throughout the whole sample period while their impacts were stronger before the Asian economic crisis in 1997. This is due to the capital control policy implemented in Malaysia after the Asian economic crisis in 1997. The relationship between stock returns and deficiency in liquidity was examined and the results show a positive significant relation between a deficient liquidity system and expected returns over 15 years. Moreover, we examined the size effect on the relation between both the liquidity apparent in big and small stock markets, and their respective returns. The results show that the effect of an illiquid market is positive and significant in each of the two sub-samples – the small and big stocks – but the coefficient of the big stock sample is significantly greater than the coefficient of the small stock sample.